Accuracy of simple clinical and epidemiological definitions of childhood obesity: systematic review and evidence appraisal. (29th September 2015) - Wilson, DC; Kelly, J; Reilly, JJ
Abstract : Introduction and Aim: The optimum means of defining obesity in children is unclear, creating variation in practice, and hindering obesity surveillance, prevention and treatment. The authors aimed to review evidence on the use of body mass index (BMI) and waist circumference for diagnosis of high body fat content and adverse cardiometabolic risk factors in children and adolescents. Methods: A systematic literature review was performed in MEDLINE and EMBASE from January 2002 to January 2008, following our last systematic review of this topic (to end 2001–2002).1 The authors collected evidence in 0–18 year olds which compared the accuracy of BMI vs waist circumference, and compared BMI interpreted relative to national reference data vs BMI interpreted relative to Cole/International Obesity Task Force (IOTF) international reference data.2 Reference lists of all eligible papers in the search and from recent guidelines on paediatric obesity were all checked manually for additional studies. Studies were only included if "diagnostic accuracy" of BMI and/or waist were reported (summary statistics such as sensitivity and specificity; area under the curve; predictive values; ROC, analysis). Evidence was appraised using the Quality Assessment of Studies of Diagnostic Accuracy in Systematic Reviews method.3 Results: Ten studies compared diagnostic accuracy of BMI vs waist circumference: they reported no improved identification of adverse cardiometabolic risk profiles from waist circumference over that provided by high BMI. Eight studies compared BMI with national reference data vs the international approach: 5/8 found significantly poorer accuracy (lower sensitivity) using BMI with the international approach; 3/8 found similar sensitivity; in 7/7 studies which compared specificity this was similar. Conclusion: The present review provides no compelling evidence for use of either high waist circumference or BMI interpreted using the IOTF approach in preference to the use of national BMI percentiles for the identification of children and adolescents with excess fatness and adverse cardiometabolic risk profile.